TELAAH FILOSOFIS PEDAGOGIS PEMIKIRAN KH. HASYIM ASYâARI DALAM KITAB ADAB AL-âALIM WA AL-MUTAâALLIM - Amrullah, Zen (Humanistika : Jurnal Keislaman, 2015)
On this modern era, most of education practitioners have perspective that the purpose of education is educating student to be more intelligent in cognitive area. Whereas, In the perspective of the founder of Nahdlatul Ulamaâ organization (NU) KH Hasyim Asyâari, the educationâs goal should be directed in educating the behavior of students. KH. Hasyim Asyâari believes that the searching of knowledge is part of glorious work in religion, so that, people who search knowledge should show glorious thing in their attitude to acquire the knowledge, and this kind of thinking is poured by KH Hasyim Asyaris in his book Adab Al-âAlim Wa Al-Mutaâallim. In this book, KH Hasyim Asyâari sees that in searching of science is as part of religion activity and it must be followed by the good attitude (al-akhlÃ¢q al-karÃ®mah). That kind of thinking is bringing KH Hasyim Asyâari has the own philosophy in education. Then, to know more about the pedagogic philosophy of KH Hasyim Asyâari, the researcher conducts literature research that highlight the thought of KH Hasyim Asyâari about education through his book, Adab Al-âAlim Wa Al-Mutaâallim. In this research is found that the concept of education focuses on attitude, the concept of education which is offered seems does not too support the development of critical logical reasoning. This thing is caused by the core of good attitude (akhlaq) and critical reasoning are opposite each other. in one side, akhlaq is most influenced by faith or believed which is sourced from heart, whereas logical reasoning is influenced by rationality which comes from brain, and that different sources will impact the out put which will be resulted.